The association between discrimination and violence among Somali Canadian youth. Issue 13 (3rd October 2018) - Ungar, Michael; Hadfield, Kristin; Amarasingam, Amarnath; Morgan, Sarah; Grossman, Michele
ABSTRACT: Analyses were conducted with a sample of 18–30-year-old Somali Canadians to test the association between discrimination and violence-related beliefs and behaviours, whether this association differs by the source of the discrimination, and whether there is a different pattern of effects for men and women. Results indicate that discrimination from within one's own community is not associated with attitudes towards violence, anti-violence behaviours or criminal violence. By contrast, out-group discrimination is associated with more anti-violence behaviours by women, although these effects are not strong. Out-group discrimination is also related to criminal violence among men but not women.